2022
DOI: 10.3390/ijms23115868
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Hypoxia Increased the Expression of DBH and PNMT in Neuroblastoma Cells via MicroRNA-375-Mediated Mechanism

Abstract: Sleep apnea syndrome (SAS), characterized by recurrent episodes of oxygen desaturation and reoxygenation (intermittent hypoxia (IH)), is a risk factor for hypertension and insulin resistance. We report a correlation between IH and insulin resistance/diabetes. However, the reason why hypertension is induced by IH is elusive. Here, we investigated the effect of IH on the expression of catecholamine-metabolizing enzymes using an in vitro IH system. Human and mouse neuroblastoma cells (NB-1 and Neuro-2a) were expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(37 citation statements)
references
References 57 publications
2
35
0
Order By: Relevance
“…The prevalence of SAS in patients with heart failure ranges from 15% to 59%, and the mortality rate among patients with severe SAS is significantly high [ 27 , 28 , 29 , 30 ]. We recently reported that IH increases renin expression in juxtaglomerular cells [ 46 ], as well as the expression of dopamine β-hydroxylase and phenylethanolamine N -methyltransferase in catecholamine-synthesizing neuroblastoma cells [ 64 ], causing SAS patients to become hypertensive. However, how cardiac dysfunction develops in SAS patients remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The prevalence of SAS in patients with heart failure ranges from 15% to 59%, and the mortality rate among patients with severe SAS is significantly high [ 27 , 28 , 29 , 30 ]. We recently reported that IH increases renin expression in juxtaglomerular cells [ 46 ], as well as the expression of dopamine β-hydroxylase and phenylethanolamine N -methyltransferase in catecholamine-synthesizing neuroblastoma cells [ 64 ], causing SAS patients to become hypertensive. However, how cardiac dysfunction develops in SAS patients remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were kept at 37 °C, 5% CO 2 , and 95% humidity, and the medium was changed every day. The cells were exposed to either normoxia (21% O 2 , 5% CO 2 , and balanced N 2 ) or intermittent hypoxia (IH: 70 cycles of 5 min sustained hypoxia (1% O 2 , 5% CO 2 , and balanced N 2 ) and 10 min normoxia) using a custom-designed, computer-controlled incubation chamber attached to an external O 2 -CO 2 -N 2 computer-driven controller (O 2 programmable control, 9200EX, Wakenbtech Co., Ltd., Kyoto, Japan), as previously described [ 4 , 40 , 46 , 64 , 80 , 81 ]. These conditions are similar to the conditions reported in patients with severe degrees of SAS; in severe SAS cases, patients are repeatedly exposed to severe hypoxemia followed by mild hypoxemia or normoxia (i.e., IH).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations